Involving children and young people in research. Issue 2 (February 2020) - Modi, Neena
Abstract: Attitudes to the participation and involvement of infants, children and young people in research have evolved over the years and will undoubtedly continue to change. Today we recognize that they have the right to benefit from research and have their care ' assured by research ', as well as the right to protection from any dangers from research participation as well as protection against the dangers of receiving non-evidenced treatments. We also recognize that they can be involved in many ways, including prioritising research questions and the outcomes that are measured, helping design studies so that they are acceptable and successful, ensuring information is comprehensible, and participating in disseminating outcomes and discussing emerging issues. Here, I provide a summary of the changes that have occurred. I explain why involvement is important, discuss how to do this, and provide tips and perspectives from children and young people themselves. I provide pointers to other sources of information and advice. Finally, I consider ways in which involvement might evolve in the future.